PENGGUNAAN MEDIA BALOK DALAM MENINGKATKAN KEMAMPUAN MENGENAL HURUF ANAK USIA DINI DI RA AL-HIDAYAH DALAN LIDANG - Nur Khofifah Lubis; Kholidah Nur; Zulfina Zulfina (CV. ADIBA ASIHA AMIRA, 2025)
This research aims to evaluate the use of block media in improving the ability to recognize letters in early childhood at RA Al-Hidayah Dalan Lidang. The method used is classroom action research which consists of two cycles, each including the stages of planning, implementation, observation and reflection. The results showed a significant increase in children's ability to name, differentiate and group letters. In cycle I, the results of observations showed that the majority of children were in the Starting to Developing to Not Yet Developing category. However, in cycle II, there was an increase, where the number of children who reached the Very Well Developing and Developing As Expected categories increased. This confirms that block media is effective in improving letter recognition in early childhood, even though there are several obstacles faced during the learning process.